Functional consequences of changes in the distribution of Ca2+ extrusion pathways between t-tubular and surface membranes in a model of human ventricular cardiomyocyte - Pásek, Michal; Bébarová, Markéta; Šimurdová, Milena; Šimurda, Jiří (Journal of molecular and cellular cardiology, 2024)
The sarcolemmal Ca2+ efflux pathways, Na+-Ca2+-exchanger (NCX) and Ca2+-ATPase (PMCA), play a crucial role in the regulation of intracellular Ca2+ load and Ca2+ transient in cardiomyocytes. The distribution of these pathways between the t-tubular and surface membrane of ventricular cardiomyocytes varies between species and is not clear in human. Moreover, several studies suggest that this distribution changes during the development and heart diseases. However, the consequences of NCX and PMCA redistribution in human ventricular cardiomyocytes have not yet been elucidated. In this study, we aimed to address this point by using a mathematical model of the human ventricular myocyte incorporating t-tubules, dyadic spaces, and subsarcolemmal spaces. Effects of various combinations of t-tubular fractions of NCX and PMCA were explored, using values between 0.2 and 1 as reported in animal experiments under normal and pathological conditions. Small variations in the action potential duration (≤ 2%), but significant changes in the peak value of cytosolic Ca2+ transient (up to 17%) were observed at stimulation frequencies corresponding to the human heart rate at rest and during activity. The analysis of model results revealed that the changes in Ca2+ transient induced by redistribution of NCX and PMCA were mainly caused by alterations in Ca2+ concentrations in the subsarcolemmal spaces and cytosol during the diastolic phase of the stimulation cycle. The results suggest that redistribution of both transporters between the t-tubular and surface membranes contributes to changes in contractility in human ventricular cardiomyocytes during their development and heart disease and may promote arrhythmogenesis.
Keywords: vápníková signalizace; biologické modely; Heart Ventricles; Cell Membrane; Calcium ATPase; Myocytes, Cardiac; Action Potentials; srdeční komory; lidé; Models, Biological; Sodium-Calcium Exchanger; NCX; Human ventricular cell model; vápník; modely kardiovaskulární; Calcium cycling; Sarcolemma; Calcium; T-tubules; Calcium Signaling; sarkolema; Sodium‑calcium exchanger; pumpa pro výměnu sodíku a vápníku; Models, Cardiovascular; buněčná membrána; PMCA; Membrane protein distribution; akční potenciály; kardiomyocyty; Humans